2023
DOI: 10.3390/ijms24033045
|View full text |Cite
|
Sign up to set email alerts
|

Culturing the Chicken Intestinal Microbiota and Potential Application as Probiotics Development

Abstract: Pure cultures of chicken intestinal microbial species may still be crucial and imperative to expound on the function of gut microbiota, and also contribute to the development of potential probiotics and novel bioactive metabolites from gut microbiota. In this study, we isolated and identified 507 chicken intestinal bacterial isolates, including 89 previously uncultured isolates. Among these, a total of 63 Lactobacillus strains, belonging to L. vaginalis, L. crispatus, L. gallinarum, L. reuteri, L. salivarius, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…Research has found that a Limosilactobacillus reuteri strain isolated from a mixture of feces, intestinal contents, and intestinal mucosa of chicken exhibited outstanding antibacterial activity against S. pullorum and fine tolerance to acid and simulated intestinal fluid. Animal experiments have shown that dietary supplementation with this strain improved weight loss, reduced the loads of S. pullorum in the intestine and viscera, and decreased intestinal inflammation of the broilers challenged with S. pullorum [56]. In the future, we will adopt animal experiments to test the effects of the Lactobacilli on the growth performance and intestinal health of chickens.…”
Section: Discussionmentioning
confidence: 99%
“…Research has found that a Limosilactobacillus reuteri strain isolated from a mixture of feces, intestinal contents, and intestinal mucosa of chicken exhibited outstanding antibacterial activity against S. pullorum and fine tolerance to acid and simulated intestinal fluid. Animal experiments have shown that dietary supplementation with this strain improved weight loss, reduced the loads of S. pullorum in the intestine and viscera, and decreased intestinal inflammation of the broilers challenged with S. pullorum [56]. In the future, we will adopt animal experiments to test the effects of the Lactobacilli on the growth performance and intestinal health of chickens.…”
Section: Discussionmentioning
confidence: 99%
“…reuteri cocultured with/without PKP were treated in acidic environment, and the density was examined in simulated gastric (pH = 1.2) and small intestine fluids (pH = 6.8) by incubation of L. reuteri in the corresponding medium for 0, 2, 4, and 6 h, respectively . To investigate the protective effect of PKP on cell density of L.…”
Section: Methodsmentioning
confidence: 99%
“…Additionally, some strains increase the nutritional value of feed by production of vitamins, exopolysaccharides, and antioxidants [15,16]. A variety of probiotics have been found to exert essential functions for improving growth performance and intestinal health in broilers, mainly including Bacillus, Enterococcus, Lactobacillus, and Clostridium [16][17][18][19]. Among that, studies reported that Limosilactobacillus fermentum can alleviate intestinal villus damage and increase serum IgM level in broilers challenged with Salmonella [20], and relieve Campylobacter coli induced inflammatory response by suppressing the secretion of cytokines and modulating lymphocyte subpopulation levels [21].…”
Section: Introductionmentioning
confidence: 99%